Pengaruh Senam Hipertensi Terhadap Peningkatan Kualitas Hidup di Posyandu Lansia Nogosaren - Siti Firani Rahmawati; Jenita Doli Tine Donsu; Bondan Palestin (Caring : Jurnal Keperawatan, 2025)
One condition that is closely associated with the aged population is hypertension. It is referred to as a "silent killer" because, although it frequently shows no symptoms, it can cause serious problems. A person's health can deteriorate due to hypertension, which can have a detrimental impact on their quality of life. 32 senior citizens at the Nogosaren Elderly Integrated Health Post (Posyandu Elderly) had hypertension in 2023, whereas 2,647 cases of hypertension were reported at the Gamping II Community Health Center. Exercise for hypertension is a type of physical activity intended for older adults with hypertension with the goals of managing stress, which is one of the primary causes of elevated blood pressure, and losing weight. Two times a week at the very least, this 30-minute workout is done. Goal: to ascertain how exercise for high blood pressure affects older people's quality of life. This study used a one-group pre-test-post-test quasi-experimental design. 32 senior citizens were chosen for the sample using total sampling. The Wilcoxon test was used to examine the data at a significance level of p < 0.05. The quality of life scores before and after the hypertension exercise intervention differed significantly, according to the statistical analysis, with a p-value of 0.000 (p ? 0.05). Elderly people's quality of life is significantly improved by hypertension exercise. It is advised that nursing care practices incorporate this intervention and that it be maintained as a long-term program in senior health services.